Myg1 exonuclease couples the nuclear and mitochondrial translational programs through RNA processing. Issue 11 (13th May 2019) - Grover, Ritika; Burse, Shaunak A; Shankrit, Shambhavi; Aggarwal, Ayush; Kirty, Kritika; Narta, Kiran; Srivastav, Rajpal; Ray, Ashwini Kumar; Malik, Garima; Vats, Archana; Motiani, Rajender K; Thukral, Lipi; et al.
Abstract: Semi-autonomous functioning of mitochondria in eukaryotic cell necessitates coordination with nucleus. Several RNA species fine-tune mitochondrial processes by synchronizing with the nuclear program, however the involved components remain enigmatic. In this study, we identify a widely conserved dually localized protein Myg1, and establish its role as a 3′-5′ RNA exonuclease. We employ mouse melanoma cells, and knockout of the Myg1 ortholog in Saccharomyces cerevisiae with complementation using human Myg1 to decipher the conserved role of Myg1 in selective RNA processing. Localization of Myg1 to nucleolus and mitochondrial matrix was studied through imaging and confirmed by sub-cellular fractionation studies. We developed Silexoseqencing, a methodology to map the RNAse trail at single-nucleotide resolution, and identified in situ cleavage by Myg1 on specific transcripts in the two organelles. In nucleolus, Myg1 processes pre-ribosomal RNA involved in ribosome assembly and alters cytoplasmic translation. In mitochondrial matrix, Myg1 processes 3′-termini of the mito-ribosomal and messenger RNAs and controls translation of mitochondrial proteins. We provide a molecular link to the possible involvement of Myg1 in chronic depigmenting disorder vitiligo. Our study identifies a key component involved in regulating spatially segregated organellar RNA processing and establishes the evolutionarily conserved ribonuclease as a coordinator of nucleo-mitochondrial crosstalk.